Release of glutamate and CGRP from trigeminal ganglion neurons: Role of calcium channels and 5-HT1 receptor signaling - Hurley Joyce H; Richter Judith A; Xiao Yan (SAGE Publishing, 2008)
Abstract Background The aberrant release of the neurotransmitters, glutamate and calcitonin-gene related peptide (CGRP), from trigeminal neurons has been implicated in migraine. The voltage-gated P/Q-type calcium channel has a critical role in controlling neurotransmitter release and has been linked to Familial Hemiplegic Migraine. Therefore, we examined the importance of voltage-dependent calcium channels in controlling release of glutamate and CGRP from trigeminal ganglion neurons isolated from male and female rats and grown in culture. Serotonergic pathways are likely involved in migraine, as triptans, a class of 5-HT1 receptor agonists, are effective in the treatment of migraine and their effectiveness may be due to inhibiting neurotransmitter release from trigeminal neurons. We also studied the effect of serotonin receptor activation on release of glutamate and CGRP from trigeminal neurons grown in culture. Results P/Q-, N- and L-type channels each mediate a significant fraction of potassium-stimulated release of glutamate and CGRP. We determined that 5-HT significantly inhibits potassium-stimulated release of both glutamate and CGRP. Serotonergic inhibition of both CGRP and glutamate release can be blocked by pertussis toxin and NAS-181, a 5-HT1B/1D antagonist. Stimulated release of CGRP is unaffected by Y-25130, a 5-HT3 antagonist and SB 200646, a 5-HT2B/2C antagonist. Conclusion These data suggest that release of both glutamate and CGRP from trigeminal neurons is controlled by calcium channels and modulated by 5-HT signaling in a pertussis-toxin dependent manner and probably via 5-HT1 receptor signaling. This is the first characterization of glutamate release from trigeminal neurons grown in culture.